A case of midgut volvulus related to adult intestinal malrotation found with weight loss after streptococcus infection: A case report and literature review. (February 2021) - Higashi, Yuri; Onishi, Ichiro; Kayahara, Masato; Kano, Shunsuke; Makita, Naoki; Munemoto, Masayoshi; Yagi, Yasumichi
Highlights: Midgut volvulus related to adult intestinal malrotation found with weight loss is rare. The development of collateral circulation from SMV to portal vein did not lead to intestinal necrosis. It's controversial whether it should be an emergency surgery or an elective surgery. In the chronic course, there is a high degree of adhesions, and countermeasures against postoperative ileus are necessary. If a patient complains of gastrointestinal symptoms, intestinal malrotation should be raised in the differential diagnosis. Abstract: Introduction and importance: The incidence of intestinal malrotation is 1 in 6000 births, and 90% of cases occur within the first year of life. Adult cases are rare, with a reported incidence of 0.2%–0.5% of all cases. The significance of reporting this case is to recognize that some adult-onset cases require surgery even in the absence of intestinal necrosis. Case presentation: A 36-year-old man was infected with streptococcus and treated with antibiotics. He developed appetite loss and his weight decreased 12 kg in 4 months. His abdomen was flat and soft with no tenderness. A computed tomography scan showed that the horizontal duodenal leg was not anchored to the retroperitoneum. Rotation of the mesentery, which was wrapped around the superior mesenteric artery in a clockwise direction, was observed, suggesting midgut volvulus. We performed emergency surgery and Ladd's procedure. Clinical discussion: A previous study reported that the most common symptom in the chronic course of intestinal malrotation was abdominal pain in 41.2% of cases, and weight loss was observed in only 2.6% of patients. The high degree of intestinal adhesion suggests that repeated torsion and release and the development of collateral vessels may have contributed to the asymptomatic course. Conclusion: Adult-onset intestinal malrotation should be considered as a differential diagnosis in the presence of weight loss and gastrointestinal symptoms. The timing of surgery is still controversial. In chronic cases, severe adhesion might be expected and laparoscopic surgery should be considered carefully.